A Prospective Randomized Controlled Study on Supraclavicular Brachial Plexus Block: Comparing Dexamethasone and Sodium Bicarbonate as Adjuvants to Local Anesthetics - Jayantilal, Shah Raj; Gupta, Sachin Kumar; Gaur, Divyansh; Raza, Ali; Shrikanta (Student's Journal of Health Research Africa, 2024)
Background: Supraclavicular brachial plexus block (SCBPB) is commonly utilized for upper limb surgeries, providing effective regional anesthesia and analgesia. Although local anesthetics are key to successful nerve blocks, the addition of adjuvants can significantly influence the onset, duration, and quality of anesthesia. Methods: A prospective randomized controlled study of 100 adult patients (ASA I–II) undergoing upper limb surgeries compared two groups: Group A (SCBPB with local anesthetic + dexamethasone 8 mg) and Group B (SCBPB with local anesthetic + sodium bicarbonate 1 mEq). Onset and duration of sensory and motor blockade, postoperative analgesia duration, and VAS scores were recorded. Data were analyzed using SPSS 23.0, with p<0.05 considered significant. Results: Compared to Group B, Group A showed a noticeably longer block duration and a much earlier onset of sensory and motor blockade (p<0.001). Group B experienced sensory block for an average of 8.2 ± 1.9 hours, while Group A had it for an average of 12.5 ± 2.3 hours (p<0.001). Group A's postoperative analgesia lasted 720 ± 150 minutes, which was significantly longer than Group B's (480 ± 130 minutes; p<0.001). At every time interval evaluated, Group A's VAS scores were consistently lower (p<0.001). There were negligible and similar side effects in each group (p>0.05). Conclusion: Dexamethasone as an adjuvant to local anesthetics in SCBPB resulted in faster onset, prolonged blockade, enhanced postoperative analgesia, and improved pain control compared to sodium bicarbonate. Both agents showed a similar safety profile. Recommendations: Dexamethasone should be considered the preferred adjuvant for improving block characteristics and patient comfort in SCBPB. Further large-scale, multicenter studies could solidify these findings and explore optimal dosing strategies.